Weekly Sequential Antibioprophylaxis for Recurrent Urinary Tract Infections Among Patients With Neurogenic Bladder: A Randomized Controlled Trial. (21st December 2019) - Dinh, Aurélien; Hallouin-Bernard, Marie-Charlotte; Davido, Benjamin; Lemaignen, Adrien; Bouchand, Frédérique; Duran, Clara; Even, Alexia; Denys, Pierre; Perrouin-Verbe, Brigitte; Sotto, Albert; Lavigne, Jean-Philippe; Bruyère, Franck; et al.
Abstract: Background: Recurrent urinary tract infections (R-UTIs) are the main cause of morbidity and hospitalizations in subjects with neurogenic bladder (NB) due to spinal cord injury (SCI). We evaluated the efficacy of weekly oral cyclic antibiotic (WOCA) prophylaxis (ie, the alternate weekly administration of 2 antibiotics) in preventing R-UTIs. Methods: Randomized (1:1), open-label, superiority-controlled trial compared WOCA prophylaxis to no prophylaxis (control) for 6 months in patients with NB due to SCI, using clean intermittent self-catheterization, and suffering from R-UTIs. Primary outcome was incidence of symptomatic antibiotic-treated UTIs. Secondary outcomes were number of febrile UTIs, number of hospitalizations, WOCA tolerance, antibiotic consumption, number of negative urine cultures, and emergence of bacterial resistance in urinary, intestinal, and nasal microbiota. Results: Forty-five patients were either allocated to the WOCA group (n = 23) or the control group (n = 22). Median (IQR) incidence of symptomatic antibiotic-treated UTIs was 1.0 (0.5–2.5) in the WOCA group versus 2.5 (1.2–4.0) ( P = .0241) in the control group. No febrile UTIs were recorded in the WOCA group versus 9 (45.0%) ( P < .001) in the control group. The median number of additional antibiotic treatment was 0.0 (IQR, 0.0–2.0) versus 3.0 (2.0–5.0) ( P = .004) in the WOCA and control groups, respectively. Only few adverse events were reported. No impact on emergence of bacterial resistance was observed. Conclusions: WOCA is efficient and well tolerated in preventing R-UTIs in SCI patients. In our study, we did not observe any emergence of antibiotic resistance in digestive and nasal microbiological cultures. Clinical Trials Registration: NCT01388413. Abstract : This open-label randomized controlled trial shows that weekly oral cyclic antibiotic prophylaxis (alternate administration of 2 different antibiotics) is efficient in preventing recurrent urinary tract infections in patients with neurogenic bladder due to spinal cord injury and well tolerated.